Teaching mathematics with the active thinking model and its impact on metacognitive thinking among the fourth literary students (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to identify (Teaching Mathematics with the Active Thinking Modeland its Impact on the Metacognitive Thinking of the Literary Fourth Students); The researchsample consisted of (60) students of the fourth literary students, distributed equally into twoexperimental and control groups of (30) students in each group. , and check its psychometricproperties; The researcher applied the test to the two research groups after the end of theexperiment, and the results showed: The students of the experimental group who studied with theactive thinking model outperformed the students of the control group who studied in the usualway in the metacognitive thinking test.